De novo PBX1 variant in a patient with glaucoma, kidney anomalies, and developmental delay: An expansion of the CAKUTHED phenotype. Issue 3 (19th November 2021) - Safgren, Stephanie L.; Olson, Rory J.; Pinto e Vairo, Filippo; Bothun, Erick D.; Hanna, Christian; Klee, Eric W.; Schimmenti, Lisa A.
Abstract: An infant was referred for evaluation of congenital glaucoma and corneal clouding. In addition, he had a pelvic kidney, hypotonia, patent ductus arteriosus, abnormal pinnae, and developmental delay. Exome sequencing identified a previously unpublished de novo single nucleotide insertion in PBX1 c.400dupG (NM_002585.3), predicted to cause a frameshift resulting in a truncated protein with loss of function (p.Ala134Glyfs*65). Identification of this loss of function variant supports the diagnosis of congenital anomalies of the kidney and urinary tract syndrome with or without hearing loss, abnormal ears, or developmental delay (CAKUTHED). Here, we propose glaucoma as an extra‐renal manifestation associated with PBX1 ‐related disease due to the relationship of PBX1 with MEIS1, MEIS2, and FOXC1 transcription factors associated with eye development.